The Effectiveness of Cadavers Compared with Mannequins on Understanding Anatomy of the Nervous System of Medical Students - Vina Alexandra Kurniasari; Yunia Hastami; Siti Munawaroh (Ahmad Dahlan Medical Journal, 2022)
Anatomy of the nervous system is one of the basic materials of medicine that is quite difficult for students to understand. One method used for learning anatomy is a practicum in the laboratory by using various media, such as cadavers and mannequins. Both of these learning media has advantages and disadvantages of each in helping students to understand anatomy material. This study aims to compare cadavers and mannequins as a medium to assist students' understanding of the anatomy of the nervous system. This research is quasi-experimental research. Sampling using cluster random sampling method amounted to 4 SGD groups of first semester students of Sebelas Maret University medical study program which were then divided into 2 groups for each given material using cadaver and mannequins. Data collection was carried out by pretest and posttest conducted before and after the material was given using cadaver or mannequins. Data analysis using the t-independent test. This study shows that there is no significant difference between the use of cadavers and mannequins in the learning process of the anatomy of the nervous system, with t-independent test values obtained significance values of more than 0.05 (significance = 0.558). We can conclude that cadavers and mannequins are equally effective for use as a tool for learning the anatomy of the nervous system. ABSTRAK Anatomi sistem saraf merupakan salah satu materi dasar kedokteran yang dinilai cukup sulit bagi mahasiswa untuk dipahami. Salah satu metode pembelajaran anatomi, yaitu dengan praktikum di laboratorium dengan menggunakan berbagai media seperti, cadaver dan manekin. Kedua media pembelajaran ini masing-masing memiliki kelebihan dan kekurangan dalam membantu proses pemahaman anatomi. Penelitian ini bertujuan untuk membandingkan cadaver dan manekin sebagai media untuk membantu pemahaman anatomi sistem saraf. Penelitian ini merupakan penelitian quasi-eksperimental. Pengambilan sampel menggunakan metode cluster random sampling berjumlah 4 kelompok SGD mahasiswa semester satu program studi kedokteran Universitas Sebelas Maret yang kemudian dibagi menjadi 2 kelompok untuk masing-masing materi diberikan menggunakan cadaver dan manekin. Pengumpulan data dilakukan dengan pretest sebelum pemberian materi dan posttest setelah pemberian materi, baik menggunakan cadaver maupun manekin. Analisis data menggunakan uji t-independen. Hasil penelitian ini menunjukkan bahwa tidak ada perbedaan yang signifikan antara penggunaan cadaver atau manekin dalam pembelajaran anatomi sistem saraf, dengan hasil signifikasi pada uji t-independen didapatkan lebih dari 0.05 (signifikasi = 0.558). Dapat kami simpulkan bahwa cadaver dan manekin sama efektifnya untuk digunakan sebagai media pembelajaran anatomi sistem saraf.